Crisis and Terror in the Age of Anxiety : 9/11, the Global Financial Crisis and ISIS - Howie, Luke; Campbell, Perri (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book confronts the issues young people face growing up in the confusion and anxiety of today's highly global society. Young people face their futures consumed with feelings of doubt, uncertainty and ambivalence. The Global Financial Crisis and the rise of the Islamic State means young people are transitioning into adulthood in a time that we call an age of anxiety. They may be the first generation to have fewer opportunities than their parents yet, despite this, they are learning to imagine other kinds of futures. These are futures where economic collapse provides opportunities for entrepreneurialism and innovation, where Islamic State does not need to pose a clear and present danger, and where political action provides hope for a better world. Dealing with the current political and economic climate and progressive campaigns such as Black Lives Matter, Howie and Campbell tackle some of the biggest threats to the future of society. An innovative and wide-reaching study, this book will be of particular interest to scholars of human geography, disaster studies, politics, and sociology.- Resumé vydavatel
Keywords: mládež; úzkost; terorismus -- sociální aspekty; finanční krize -- sociální aspekty; youth; anxiety; terrorism -- social aspects; financial crises -- social aspects; elektronické knihy; monografie; electronic books; monographs